2008
DOI: 10.1111/j.1750-3841.2008.00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Gelling Properties of Lizardfish Mince as Influenced by Microbial Transglutaminase and Fish Freshness

Abstract: The effects of microbial transglutaminase (MTGase) at different levels (0 to 0.8 units/g sample) on the properties of gels from lizardfish (Saurida undosquamis) mince set at 25 degrees C for 2 h or 40 degrees C for 30 min prior to heating at 90 degrees C for 20 min were studied. Breaking force and deformation of gels increased with increasing MTGase amount added (P<0.05). At the same MTGase level used, gels with the prior setting at 40 degrees C for 30 min showed a higher breaking force compared with those sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 29 publications
4
24
0
Order By: Relevance
“…Additionally, it has been successfully used in surimi to strengthen the gel. Benjakul et al (2008) reported that the addition of MTGase from Streptoverticillium mobaraense in mince from lizardfish effectively increased breaking force and deformation of gel.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, it has been successfully used in surimi to strengthen the gel. Benjakul et al (2008) reported that the addition of MTGase from Streptoverticillium mobaraense in mince from lizardfish effectively increased breaking force and deformation of gel.…”
Section: Introductionmentioning
confidence: 98%
“…However, effectiveness in improving the gel quality varied with surimi. Different intrinsic factors such as level of proteases, fat content, endogenous transglutaminase, etc., play a role in determining gelation of surimi as well as efficacy in gel improvement by protein additives (Benjakul, Phatcharat, Tammatinna, Visessanguan, & Kishimura, 2008;Benjakul & Visessanguan, 2003;Benjakul, Visessanguan, & Pecharat, 2004;Benjakul, Visessanguan, & Srivilai, 2007;Campo-Deaño & Tovar, 2009;Duangmal & Taluengphol, 2009;Rawdkuen et al, 2008). Microbial transglutaminase (MTGase) has been widely used to improve the textural quality of several foods such as ham, sausage, tofu, and noodles (Motoki & Seguro, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Expressible moisture content Expressible moisture content (%) was measured according to the method of Benjakul et al (2008). Cylindrical gel samples were cut into a thickness of 5 mm, weighed (X), and placed between 2 pieces of Whatman paper no.…”
Section: Analysesmentioning
confidence: 99%
“…Microbial transglutaminase (MTGase) has been widely used in processed fish and meat in order to strengthen protein-based gels. MTGase has been reported to increase gel strength of surimi from different fish such as lizardfish (Benjakul et al 2008), threadfin bream (Benjakul et al 2004;Jiang et al 2000), and sardine (Kudre and Benjakul 2013;Karayannakidis et al 2008). Efficiency of MTGase in improving gel properties of proteins depends on many factors, e.g., the amount of MTGase as well as protein substrates (Asagami et al 1995;DeJong and Koppelman 2002).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, gel formation is generally decreased with increasing storage or handling time. Benjakul et al 119 found that MTGase was a powerful gel enhancer of mince from lizardfish stored in ice for different times. However, the gel enhancing ability was greater in surimi produced from fresh lizardfish (see Fig.…”
Section: Use Of Mtgase In Surimi and Fish Mince Gelsmentioning
confidence: 99%